From social determinants to social interdependency: Theory, reflection, and engagement - William Ventres; Shafik Dharamsi; Robert Ferrer (Social Medicine Publication Group, 2017)
Introduction Scholars and practitioners in medicine and public health have devoted significant time and effort to defining the social determinants of health and identifying resulting inequities in health outcomes. By focusing predominately on social determinants as referent sources of morbidity and mortality, however, health care professionals can be led to believe that the origins of poor health-related outcomes are disconnected from the ways in which social, economic, political, and environmental factors are established and maintained. Discussion We introduce the concept of social interdependency in health ¬and illness as a way to (1) reinforce the need to consider the root causes of social determinants, and (2) accepting communal and personal responsibility for acting to ameliorate their effects. Developing a sound understanding of social interdependency in clinical practice, public health research, and health care advocacy involves an iterative process of observation, reflection, and action. Effecting positive change within these disciplines is a shared obligation. We present a case study that demonstrates these principles of social interdependency. Conclusion Developing and applying a social interdependency in health and illness means moving from imposition to inclusivity, from investigation to involvement, and from investment in medicine and public health as a product to one of process. This process-the movement from social determinants toward social interdependency-showcases how we live in a world where none of us is so separate from another that we cannot benefit by envisioning and desiring for others what we might desire for ourselves.